Assessing and reassessing responses to pain management - Wertheimer, Debra; Whiteford-Hadary (Firm) (Baltimore, Md. : VideoPress, 2002)
(Producer) Dr. Wertheimer stresses the importance of on-going assessment and re-assessment of residents to ensure that pain management is affective. As physicians and nursing staff depend on the observations of the nursing assistants, their role assumes utmost importance. The team needs to know if pain medications are providing needed relief, and if there are side-effects to the medications. When there are side-effects, it's essential to be able to communicate what those side effects are. In addition to medications, addresses splints, positioning, cushions, and other methods of managing pain.
Content, Debra Wertheimer ; producer/writer, Susan Hadary
Presented by Debra Wertheimer
VHS
Keywords: Pain -- Diagnosis; Nurses' Aides; Nursing Assessment; Pain -- Therapy